Myosin7a deficiency results in reduced retinal activity which is improved by gene therapy. - Pasqualina Colella; Andrea Sommella; Elena Marrocco; Umberto Di Vicino; Elena Polishchuk; Marina Garcia Garrido; Mathias W Seeliger; Roman Polishchuk; Alberto Auricchio (PLoS ONE, 2013)
Mutations in MYO7A cause autosomal recessive Usher syndrome type IB (USH1B), one of the most frequent conditions that combine severe congenital hearing impairment and retinitis pigmentosa. A promising therapeutic strategy for retinitis pigmentosa is gene therapy, however its pre-clinical development is limited by the mild retinal phenotype of the shaker1 (sh1(-/-)) murine model of USH1B which lacks both retinal functional abnormalities and degeneration. Here we report a significant, early-onset delay of sh1(-/-) photoreceptor ability to recover from light desensitization as well as a progressive reduction of both b-wave electroretinogram amplitude and light sensitivity, in the absence of significant loss of photoreceptors up to 12 months of age. We additionally show that subretinal delivery to the sh1(-/-) retina of AAV vectors encoding the large MYO7A protein results in significant improvement of sh1(-/-) photoreceptor and retinal pigment epithelium ultrastructural anomalies which is associated with improvement of recovery from light desensitization. These findings provide new tools to evaluate the efficacy of experimental therapies for USH1B. In addition, although AAV vectors expressing large genes might have limited clinical applications due to their genome heterogeneity, our data show that AAV-mediated MYO7A gene transfer to the sh1(-/-) retina is effective.